2013
DOI: 10.3747/co.20.1540
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation after Surgery for Breast Cancer Patients with Primary Tumours and One to Three Positive Axillary Lymph Nodes: Yes or No?

Abstract: Objective and Methods: We retrospectively analyzed clinicopathologic features and survival in breast cancer patients who had T1 or T2 primary tumours and 1–3 histologically involved axillary lymph nodes and who were treated with modified radical mastectomy without adjuvant radiotherapy (RT). We also explored prognosis to find the high- and low-risk groups. Results: From May 2001 to April 2005, 368 patients treated at Tianjin Tumor Hospital met the study criteria. The 5- and 8-year rates were 7.2% and 10.7% for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 29 publications
(20 reference statements)
0
12
0
Order By: Relevance
“…Until more definitive evidence is available, using its best clinical opinion, the panel recommends that such a strategy or risk estimation include assessment of patient age as it affects the risk of LRF,7,10,21,22,38,39 estimated life expectancy in relation to age and comorbid conditions that might reduce life expectancy4044 or increase the risk of complications,4549 tumor size,6,7 axillary lymph node burden (number of positive nodes,9,16,19,22 nodal ratio,10,20,22,38 and size of nodal tumor deposits16,17,19), tumor grade,11,16,20,22,38,50 lymphovascular invasion,10,16,21,22,38,51 biomarker or receptor status,7,8,16,22,38,5256 and planned systemic therapy (Data Supplement provides discussions of these and additional factors, such as margin status57,58 and extranodal extension16,19,20). Several groups have proposed prognostic models to estimate the risk of LRF after mastectomy by combining several of these factors 10,16,20,22,38. Although the panel cannot endorse any specific model, because the models have yet to be validated, physicians may find them useful in explaining the benefits of PMRT.…”
Section: Recommendationsmentioning
confidence: 99%
“…Until more definitive evidence is available, using its best clinical opinion, the panel recommends that such a strategy or risk estimation include assessment of patient age as it affects the risk of LRF,7,10,21,22,38,39 estimated life expectancy in relation to age and comorbid conditions that might reduce life expectancy4044 or increase the risk of complications,4549 tumor size,6,7 axillary lymph node burden (number of positive nodes,9,16,19,22 nodal ratio,10,20,22,38 and size of nodal tumor deposits16,17,19), tumor grade,11,16,20,22,38,50 lymphovascular invasion,10,16,21,22,38,51 biomarker or receptor status,7,8,16,22,38,5256 and planned systemic therapy (Data Supplement provides discussions of these and additional factors, such as margin status57,58 and extranodal extension16,19,20). Several groups have proposed prognostic models to estimate the risk of LRF after mastectomy by combining several of these factors 10,16,20,22,38. Although the panel cannot endorse any specific model, because the models have yet to be validated, physicians may find them useful in explaining the benefits of PMRT.…”
Section: Recommendationsmentioning
confidence: 99%
“…Several groups have proposed prognostic models to estimate the risk of LRF after mastectomy by combining several of these factors. 10,16,20,22,38 Although the panel cannot endorse any specific model, because the models have yet to be validated, physicians may find them useful in explaining the benefits of PMRT. Further research is needed on these models and how to accurately estimate an individual's risk of LRF and hence the potential reduction in LRF and breast cancer mortality.…”
Section: Literature Review and Analysismentioning
confidence: 99%
“…In a meta-analysis, van Wely et al 32 also found that patients with abnormal alns on imaging had a higher risk of having multiple metastatic lymph nodes. Patients with multiple metastatic lymph nodes might need postmastectomy radiotherapy to lower the recurrence rate 33,34 .…”
Section: Discussionmentioning
confidence: 99%